Morphologic Features of Myopic Choroidal Neovascularization in Pathologic Myopia on Swept-Source Optical Coherence Tomography - Xie, Jiamin; Chen, Qiuying; Yu, Jiayi; Zhou, Hao; He, Jiangnan; Wang, Weijun; Fan, Ying; Xu, Xun (Frontiers in Medicine, 2020)
Purpose: To investigate the morphologic features and identify the risk factors of myopic choroidal neovascularization (CNV). Methods: Eighty-eight eyes of 69 consecutive patients with myopic CNV were included in this study. About 109 eyes of 78 pathologic myopia patients without myopic CNV were randomly selected as the control group. Morphologic features and parameters including scleral thickness (ST), choroidal thickness (CT), posterior staphyloma height and the presence of scleral perforating vessels were obtained and measured by swept-source optical coherence tomography (SS-OCT). Binary logistic regression analysis was performed to identify the risk factors for myopic CNV. Results: Patients with myopic CNV had relatively shorter axial length (P < 0.001) and thicker sclera (P < 0.001) compared to those without. After adjusting age, gender and axial length, thick sclera (OR = 1.333, P < 0.001 per 10-μm increase) and thin choroid (OR = 0.509, P < 0.001 per 10-μm increase) were associated with the presence of myopic CNV. Scleral perforating vessels were detected in the area of myopic CNV in 78.67% of the subjects. Conclusions: A relatively thicker sclera and a thinner choroid are the biological indicators for myopic CNV on SS-OCT. Scleral perforating vessels may also play a pivotal role in the formation of myopic CNV.